2018
DOI: 10.1080/07352166.2017.1406786
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of city-specific factors on social integration of Chinese migrant workers: A study using multilevel modeling

Abstract: Rural migrants in China often face obstacles that prevent them from integrating economically and socially into their host cities. We explore the effects of host city-specific factors on the social integration of migrant workers in this article. To do this, we use a survey data set that includes a sample of migrants in nine cities in eastern and central China. We estimate a multilevel linear model (MLM), taking into account both individual and city characteristics; in the first place, we show that female, highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…This paper partially confirms previous results indicating that the per capita GDP and housing costs of a receiving city negatively affect migrant integration [ 9 ]. We find that housing prices negatively affect migrant integration, that per capita GDP has no significant effect based on national survey data, and that a city’s wage level has a positive effect on migrant integration.…”
Section: Discussion: Policy Implicationssupporting
confidence: 90%
See 2 more Smart Citations
“…This paper partially confirms previous results indicating that the per capita GDP and housing costs of a receiving city negatively affect migrant integration [ 9 ]. We find that housing prices negatively affect migrant integration, that per capita GDP has no significant effect based on national survey data, and that a city’s wage level has a positive effect on migrant integration.…”
Section: Discussion: Policy Implicationssupporting
confidence: 90%
“…Fourth, the geographical paradigm addresses the impact of city-specific factors on the integration of Chinese migrant workers. The roles of dialect, city size, employment opportunities and education in receiving cities have been evaluated [ 9 ]. Generally, both migrant factors and unique macroinstitutional environmental or microcity features have an important impact on migrant integration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies on the social integration of China's migrants, Tian et al (2019) also reckoned that the specific city factor could affect the status of urban destination. Zheng et al (2020) studied and discovered that the migrants lived in the economically affordable housing showed higher social integration level than those migrants lived in other types of housing.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Current studies have found that female migrants in cities are more likely to choose to settle down. Younger people, who have fewer family commitments, less attachment to the countryside but a greater desire for urban lifestyle, are more willing to move to and settle in cities than their older counterparts (Guan, Wei, Lu, Dai, & Su, 2018;Huang, Guo, & Cheng, 2018;Liu, Deng, & Song, 2018;Mohabir et al, 2017;Tang, Hao, & Huang, 2016;Tian, Tian, & Sun, 2019;Zhang, Druijven, & Strijker, 2017;Zhu & Chen, 2010). Besides, compared to older generations, younger rural migrants tend to be less willing to live in towns compared with cities (Tang & Feng, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%